Belt and Road Sentiment Index - Lee, Liane Wai Ying; Chan, Kara; Leung, Tak Yan; Sharma, Piyush (2020)
The Chinese government has launched the Belt and Road Initiative (B&RI), targeting to establish a foreign policy scheme that facilitates infrastructure and economic development through cooperation and risk avoidance. To date, 123 countries have participated in the B&R Initiative (Zhu, 2019). These countries, together, constitute two-third of world population and one-third of global GDP. Since the implementation of B&RI, the public’s sentiment is mixed due to participating countries’ stakeholders are uncertain if unsure B&RI would benefit or disadvantage their own / countries’ interests. B&R partner countries and companies when faced with information uncertainties can retort to the use of a proposed Belt and Road Sentiment Index to achieve information symmetry. This study aims at conceptualizing the B&R sentiment construct as well as a B&R Sentiment Index to improve the information symmetry about B&R initiative among the partner countries. With enhanced information symmetry, with trustworthy information among the stakeholders, the sentiment index could be used as a tool for B&R partner countries to be prepared to enter into long-term trade relationships with China. This project can also assist the public and the media to report and disseminate information about B&RI. With enhanced public awareness, it allows the fourth estate to access information and improves the public knowledge of the myths of B&RI.